Development and Implementation of a Tool to Assess Patient-Reported Outcome Measures (PROM) in Preoperative Setting - Sunghye Kim; Pamela W Duncan; Leanne Groban; Hannah Segal; Rica Moonyeen Abbott; Jeff D Williamson (Global Journal of Perioperative Medicine - Peertechz Publications, 2017)
Introduction: Traditional preoperative assessment tools use patients' comorbidities to predict surgical outcomes, however, some functional, social and behavioral factors are known to predict surgical outcomes. Capturing functional, social and behavioral factors by incorporating patient reported measures (PROMs) into preoperative practice may be responsive to perioperative management and contribute to improved outcomes. Methods: We developed a preoperative PROM tool to identify functional, social, and behavioral factors. We describe the development and implementation of the tool as a health system quality initiative. We also report the results of the PROMs among preoperative surgical patients. Results: In our survey of 162 patients with mean age of 65, 53% were female, 29% were undergoing orthopedic surgery 12% were undergoing urologic surgery. 56% of the patients had at least one or more deficits in social or functional domain. The most common deficit was with ADLs with higher rate of deficit with advanced age. Conclusion: Implementation of a systematic assessment of functional and social determinants to improve processes of care in the preoperative setting is feasible. The majority of preoperative patients had at least one deficit and if identified preoperatively, appropriate interventions can be offered through well-designed intervention algorithms.